1984
DOI: 10.1007/bf00485853
|View full text |Cite
|
Sign up to set email alerts
|

Variation among chicken stocks in the fractional rates of muscle protein synthesis and degradation

Abstract: Fractional rates (% X day-1) of synthesis and degradation were determined by measuring the output of N tau-methylhistidine (MeHis) in the excreta at 4 and 8 weeks of age in the chicken. At 4 weeks of age, the fractional rate of synthesis of the meat-type stock was twice that of the egg-type stock (White Leghorn), but the fractional rates of synthesis at 8 weeks of age were similar (4.1-5.1% X day-1) among stocks. The fractional rate of degradation (1.3-1.5% X day-1) of the meat-type stock at 8 weeks of age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Selective breeding of broiler chickens for meat production has led to the generation of strains with accelerated growth rates, in particular which exhibits enhanced growth of the pectoralis (breast) muscle (Griffin and Goddard, 1994, Emmerson, 1997, Konarzewski et al, 2000, Berri et al, 2001. The high rate of accumulation of breast muscle protein in rapidly growing broiler chickens appears to be achieved almost entirely by a marked decrease in the fractional rate of protein degradation (Maeda et al, 1984, Hayashi et al, 1985. In this context, the expression of atrogin-1/MAFbx in different types of muscle fibers (slow-and fast-twitch muscles) and in broiler chickens requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective breeding of broiler chickens for meat production has led to the generation of strains with accelerated growth rates, in particular which exhibits enhanced growth of the pectoralis (breast) muscle (Griffin and Goddard, 1994, Emmerson, 1997, Konarzewski et al, 2000, Berri et al, 2001. The high rate of accumulation of breast muscle protein in rapidly growing broiler chickens appears to be achieved almost entirely by a marked decrease in the fractional rate of protein degradation (Maeda et al, 1984, Hayashi et al, 1985. In this context, the expression of atrogin-1/MAFbx in different types of muscle fibers (slow-and fast-twitch muscles) and in broiler chickens requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of muscle protein, a key step in muscle growth, is determined by the balance between the rates of protein synthesis and degradation. The high rate of accumulation of breast muscle protein in rapidly growing broiler chickens appears to be achieved almost entirely by a marked decrease in the fractional rate of protein degradation (Maeda et al, 1984, Hayashi et al, 1985. However, the mechanism underlying the reduced protein degradation rate in the pectoralis muscle of broiler chickens has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the fractional rate of degradation of muscle protein was by the method described by Maeda et al (1984Maeda et al ( , 1986. Complete 24-hr excreta collections were individually obtained for 3 days at 2 and 10 weeks of age and stored at -20°C until analyzed for N~-methylhistidine (N'-MH) content.…”
Section: Measurement Of the Fractional Rate Of Muscle Protein Degradamentioning
confidence: 99%
“…The muscle protein turnover rates are affected by not only physiological factors but also genetic factors. The genetic basis for the fractional rates of muscle protein turnover was demonstrated by variations among breeds and lines in the muscle protein turnover rate (Maeda et al, 1984(Maeda et al, , 1986, the effect of a single gene on the muscle protein turnover rate (Maeda et al, 1987a,b), the heterosis effects of the muscle protein turnover rate (Maeda et al, 1988), and genetic parameters of muscle protein turnover rate (Maeda et al, 1989). Recently, Maeda et al (1989) demonstrated that the protein turnover rate in muscle was associated with growth and feed utilization and, additionally, that it may be a characteristic of selection for growth and feed utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic bases of rates of muscle protein turnover have been emphasized by MAEDA et al (1984MAEDA et al ( , 1986MAEDA et al ( , 1991b. The muscle protein degradation rates of layer chickens are higher than those of broiler one, and exhibited downward trends with aging of chickens (HAYASHI et al, 1985;MAEDA et al, 1990).…”
Section: Introductionmentioning
confidence: 99%